Peningkatan Literasi Digital Guru Matematika melalui Pelatihan Articulate Storyline dalam Menyusun Media Interaktif di Lombok Barat - Ratna Yulis Tyaningsih; Ketut Sarjana; Baidowi Baidowi; Ni Made Intan Kertiyani; Luluk Wazila (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
Digital literacy has become an essential competency for teachers in developing innovative and interactive learning media. However, many mathematics teachers still face challenges in utilizing digital technology effectively for instructional purposes. This community service program aimed to enhance the digital literacy of mathematics teachers through training on the use of Articulate Storyline for developing interactive learning media. The program was conducted at SMPN 1 Sekotong and involved 14 junior high school mathematics teachers who are members of the MGMP Mathematics of West Lombok Regency. The implementation stages included needs analysis, material presentation, demonstrations, hands-on practice, mentoring, and evaluation. The training materials covered digital literacy concepts, the features of Articulate Storyline, and techniques for developing mathematics learning media that integrate multimedia elements and interactive quizzes. Evaluation was conducted through pretests and posttests to measure participants’ improvement in understanding. The results indicated that the training successfully enhanced participants’ competencies in utilizing digital technology for mathematics instruction. Based on the evaluation results, participants’ understanding increased by 4.06% from the pretest to the posttest. Furthermore, all participants successfully developed interactive learning media that could be implemented in classroom learning. The high level of participation and engagement demonstrated that the training was relevant to teachers’ professional needs. This program contributed positively to improving mathematics teachers’ digital literacy and professional competence while supporting the implementation of more effective, creative, and student-centered learning practices.